Ethem beu Mosque, Tirana, a sparkle of Islamic architecture in Albania - Soomro, Ali Raza; Aripin, Srazali; Basha, Brunilda (2014)
With the advent of Islam as a religion in Albania, Islamic architecture was developed in parallel with the events during that time. In the period when the centralization of the Turkish Empire had reached its peak, during fifteen and sixteen (XV-XVI) centuries, Ottoman art in Albania was very significant in religious buildings.